Effects of different interval-training programs on cycling time-trial performance - Stepto, N. K.; Hawley, J. A.; Dennis, S. C.; Hopkins, W. G. (Medicine & Science in Sports & Exercise, 1999)
Interval training with work bouts close to race-pace enhance 1-h endurance performance; work bouts at much higher intensity also appear to improve performance, possibly by a different mechanism.